2017
DOI: 10.1542/peds.2016-2838
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Exposures Are Associated With Risk for Pediatric-Onset Multiple Sclerosis

Abstract: Cesarean delivery and maternal health during pregnancy may influence risk for pediatric-onset MS. We report a new possible association of pesticide-related environmental exposures with pediatric MS that warrants further investigation and replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 49 publications
1
51
1
4
Order By: Relevance
“…Investigating occupational exposures may also elucidate environmental associations and risk for MS. We previously reported increased risk of pediatric‐onset MS in participants whose fathers had worked in agricultural occupations during the perinatal period 11. While data are limited, an Australian case‐control study of adults showed that some occupational exposures were strongly associated with increased risk of a first CNS demyelinating event, itself often followed by MS 14.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Investigating occupational exposures may also elucidate environmental associations and risk for MS. We previously reported increased risk of pediatric‐onset MS in participants whose fathers had worked in agricultural occupations during the perinatal period 11. While data are limited, an Australian case‐control study of adults showed that some occupational exposures were strongly associated with increased risk of a first CNS demyelinating event, itself often followed by MS 14.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our prior observations linking pediatric MS onset to certain environmental exposures just prior to pregnancy and through the first year of life. 11 An ecological study investigating the potential link between environmental pesticide exposures and various neurologic and psychiatric conditions in southern Spain, reported an increased prevalence of adult MS in areas of high, compared to low, agricultural pesticide exposure (OR 1.23, 95% CI 1.05-1.43). 12 Other environmental exposures, such as heavy metals and solvents, exhibited a stronger association with MS. 12 Pesticides and other environmental toxic agents have been associated with neurodegeneration possibly due to effects of reactive oxygen species in nerve tissue, based on animal studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations